Neuroprotective Effect of Oridonin on Traumatic Brain Injury via Inhibiting NLRP3 Inflammasome in Experimental Mice - Yan, Chaolong; Yan, Huiying; Mao, Jiannan; Liu, Yutong; Xu, Li; Zhao, Hongting; Shen, Jiaqi; Cao, Yan; Gao, Yongyue; Li, Kuanyu; Jin, Wei (Frontiers in Neuroscience, 2020)
NLRP3 inflammasome has been considered as an important contributor to inflammation and neuronal death after traumatic brain injury (TBI). Oridonin (Ori), the major active ingredient of Chinese herbal medicine Rabdosia rubescens, has been proved to be a covalent NLRP3 inhibitor with strong anti-inflammation activity. The purpose of this study was to investigate the effect of Ori on inflammation and brain injury induced by TBI. Adult male C57BL/6 mice were subjected to closed-head injury using Hall’s weight-dropping method. Oridonin was injected directly intraperitoneally (IP) at the dose of 10 mg/kg within 30 mins after TBI and injected once daily until the experiments ended. Our results showed that NLRP3 inflammasome was activated within 24 h post TBI. The expression of NLRP3 inflammasome components (NLRP3, ASC and caspase-1) was significantly decreased after treatment with Ori. Besides, the secretion of IL-1β and IL-18, downstream inflammatory factors of activated caspase-1, was reduced by Ori-treatment. Importantly, Ori administration further protected blood brain barrier, alleviated brain edema, reduced cortical lesion volume, decreased cell death and attenuated neurological deficits after TBI. Our findings indicate that NLRP3 inflammasome participated in the secondary injury after TBI and the application of Ori may provide neuroprotection via inhibiting NLRP3 inflammasome in animal models, suggesting that Ori might be a promising candidate for patients with TBI.